Electrochemical surface reconstructed Ptx(x=2, 3)Si/PtSi/p-Si photocathodes for achieving high efficiency in photoelectrochemical H2 generation. Issue 9 (11th February 2022) - Zhang, Haoyue; She, Guangwei; Xu, Jing; Li, Shengyang; Liu, Yun; Luo, Jun; Shi, Wensheng
Abstract : ESR converted the PtSi to Pt x ( x =2, 3) Si with high electrocatalytic activity for HER. Combined with the high Schottky barrier caused by DS, the Pt x ( x =2, 3) Si/PtSi/p-Si exhibited excellent PEC H2 generation performance, achieving ABPE as high as 5.8%. Abstract : Using Si-based photoelectrodes to generate H2 through photoelectrochemical (PEC) water splitting has attracted extensive attention in recent years. To produce H2 with a high efficiency, the key issues that need to be solved are the relatively low photovoltage of the Si-based photoelectrode and the sluggish kinetics of the H2 generation reaction occurring on the surface of Si. In this study, we designed and fabricated the Pt x ( x =2, 3) Si/PtSi/p-Si photocathode for high-efficiency H2 generation via PEC. The theoretically lower PtSi/p-Si junction Schottky barrier height was elevated to a high value of 0.9 eV by dopant segregation, thereby obtaining a high photovoltage. Upon the electrochemical surface reconstruction of PtSi, a thin layer of Pt x ( x =2, 3) Si with a high catalytic activity is in situ formed on the photocathode which significantly enhances the hydrogen evolution reaction (HER) kinetics. Accordingly, a favorable onset potential for HER of 0.54 V vs. RHE and a high saturated photocurrent density of 30 mA cm −2 at 0 V vs. RHE are achieved from the Pt x ( x =2, 3) Si/PtSi/p-Si photocathode. The applied-bias photo-to-current efficiency (ABPE) of the Pt x ( x =2, 3) Si/PtSi/p-Si photocathode reaches a maximum at 5.8%, which is record-high for the Si-based single junction photocathodes without a buried p–n junction. Moreover, the Pt x ( x =2, 3) Si/PtSi/p-Si photocathode exhibits an excellent stability in the long-term PEC H2 generation test. This work provides a new perception onto the design and construction of Si-based photocathodes with improved catalytic activity, as well as the possibility of efficient and stable PEC H2 generation.